Enhancing patient experience by training local trainers in fundamental communication skills - Calvin Chou (The Beryl Institute, 2014)
Medical centers have a vested interest in improving patient experience through enhancing communication skills. The American Academy on Communication in Healthcare has helped institutions across the country establish internal expertise through delivering train-the-trainer programs. The phases of the program include preparing for implementation of the program, having program participants undergo a fundamental communication skills workshop and then understanding the theoretical and practical rationales underlying the workshop, setting up practice sessions for participants to achieve mastery, and ensuring long-term viability of a communication skills improvement initiative. Outcomes for participants include increased self-assessed personal communication skill, optimism about rolling out a communication skills program, and enhanced communication and hopefulness in working with colleagues. Train-the-trainer programs are a viable way to create enduring communities of local experts who can implement and support institutions’ commitments to excellence in the communication skills of their providers.